Genomic and functional insights into commensal streptococci with anti-pneumococcal activity - Sara Handem; Bárbara Ferreira; Carina Valente; Raquel Sá-Leão (BMC Genomics)
Abstract Background Streptococcus pneumoniae (pneumococcus), S. mitis, and S. oralis are closely related bacteria that colonize the human upper respiratory tract. While pneumococcus is a leading cause of global morbidity and mortality, S. mitis and S. oralis are generally considered commensals, rarely causing disease in immunocompetent hosts. Here, we characterized the genomes of seven commensal streptococcal strains (S. oralis A22 and S. mitis B22–G22) identified as potential biotherapeutics due to their bacteriocin-mediated antipneumococcal activity. Results Comparative genomic analyses revealed key differences between these commensals and pneumococci. Commensal strains encode diverse adhesin-like proteins, absent in pneumococci, and lack key virulence factors such as pilus islets and pneumococcal surface proteins. They also possess extensive restriction-modification and type II toxin-antitoxin systems, alongside novel prophages, suggesting roles in genetic stability and phage defense. Metabolic adaptations in commensals indicate a “cheater” strategy, relying on extracellular metabolites from other microorganisms, particularly in the nutrient-scarce nasopharynx. Additionally, commensal strains exhibit distinct teichoic acid compositions, with galactose-rich lipoteichoic acids potentially enhancing niche adaptation. Capsular diversity was also observed, with some strains encoding unique polysaccharides. These findings highlight genomic features that likely enhance commensal colonization and survival in the upper respiratory tract, while distinguishing them from pneumococci. Conclusions This study highlights the genomic characteristics of the seven commensal streptococcal strains with broad anti-pneumococcal activity recently described and provides insights into species-specific traits that could inform targeted strategies for pneumococcal control.